Model-based fractionation of biomass in a biological nutrient removal system and its effect on the removal efficiencies - Manav-Demir, Neslihan (SPRINGER, 2023)
Fractionation of active biomass in a five-stage Bardenpho process was accomplished using an MS Excel wastewater treatment plant modeling tool based on Activated Sludge Model No. 3 extended with a bio-P module. The biomass fractions within the treatment system were predicted as autotrophs, ordinary heterotrophs, and phosphorus accumulating organisms (PAOs). Several simulations were performed in a Bardenpho process using various C/N/P ratios in primary effluent. Biomass fractionation was obtained from steady-state simulation results. The results suggest that the mass percentage of autotrophs, heterotrophs, and PAOs in active biomass range from 1.7 to 7.8%, 5.7-69.0%, and 23.2-92.6%, respectively, depending on characteristics of primary effluent. Results of principal component analysis showed that TKN/COD ratio in primary effluent determines the population of autotrophs and ordinary heterotrophs whereas PAO population is mainly a function of TP/COD ratio.
Keywords: Autotrophs; Heterotrophs; Phosphorus accumulating organisms; Principal component analysis; Wastewater treatment; WASTE-WATER TREATMENT; ACTIVATED-SLUDGE; MICROBIAL COMMUNITY; NITROGEN REMOVAL; PERFORMANCE; NITRIFIERS; TOXICITY; DYNAMICS; KINETICS; PLANT; Engineering; Environmental Sciences & Ecology